Human Capital and Growth: Specification Matters. (13th November 2014) - Sunde, Uwe; Vischer, Thomas
<x xml:space="preserve">Abstract</x> This paper suggests that the weak empirical effect of human capital on growth in existing cross‐country studies is partly the result of an inappropriate specification that does not account for the different channels through which human capital affects growth. A systematic replication of earlier results from the literature shows that both initial levels and changes in human capital have positive growth effects, while in isolation each channel often appears insignificant. The results suggest that the effect of human capital is likely to be underestimated in empirical specifications that do not account for both channels.